Cost-Savings Achieved in Two Semesters Through the Adoption of Open Educational Resources - Hilton III, John Levi; Robinson, T. Jared; Wiley, David; Ackerman, J. Dale (International Review of Research in Open and Distributed Learning, 2014)
Textbooks represent a significant portion of the overall cost of higher education in the United States. The burden of these costs is typically shouldered by students, those who support them, and the taxpayers who fund the grants and student loans which pay for textbooks. Open educational resources (OER) provide students a way to receive high-quality learning materials at little or no cost to students. We report on the cost savings achieved by students at eight colleges when these colleges began utilizing OER in place of traditional commercial textbooks.